What “Family Affair?” Domestic Violence Awareness in China - Zhaohui Su; Dean McDonnell; Ali Cheshmehzangi; Ali Cheshmehzangi; Junaid Ahmad; Hengcai Chen; Sabina Šegalo; Yuyang Cai; Yuyang Cai (Frontiers in Public Health, 2022)
IntroductionDomestic violence is toxic to society. With approximately one in three women on average falling victim to domestic violence, systematic solutions are needed. To further complicate the issue, mounting research shows that COVID-19 has further exacerbated domestic violence across the world. Situations could be even more pronounced in countries like China, where though domestic violence is prevalent, there is a dearth of research, such as intervention studies, to address the issue. This study investigates key barriers to domestic violence research development in China, with a close focus on salient cultural influences.MethodsA review of the literature on domestic violence in China in PubMed, PsycINFO, and Scopus was conducted to answer the research question. The search was focused on three themes, domestic violence, China, research, and cultural influences.ResultsThe study findings show that categorizing domestic violence as a “family affair” is a key barrier to domestic violence research development in China—an incremental hindrance that prevents the public and policymakers from understanding the full scale and scope of domestic violence in China. In addition to abusers, witnesses, and victims, even law enforcement in China often dismisses domestic violence crimes as “family affairs” that resides outside the reach and realm of the law. The results indicated that mistreating domestic violence crimes as “family affairs” is a vital manifestation of the deep-rooted cultural influences in China, ranging from traditional Confucian beliefs in social harmony to the assumed social norms of not interfering with other people's businesses.ConclusionDomestic violence corrupts public health and social stability. Our study found that dismissing domestic violence cases as “family affairs” is an incremental reason why China's domestic violence research is scarce and awareness is low. In light of the government's voiced support for women's rights, we call for the Chinese government to develop effective interventions to timely and effectively address the domestic violence epidemic in China.